Multisensory Interactive Technologies for Primary Education: From Science to Technology - Volpe, Gualtiero; Gori, Monica (Frontiers in Psychology, 2019)
While technology is increasingly used in the classroom, we observe at the same time that making teachers and students accept it is more difficult than expected. In this work, we focus on multisensory technologies and we argue that the intersection between current challenges in pedagogical practices and recent scientific evidence opens novel opportunities for these technologies to bring a significant benefit to the learning process. In our view, multisensory technologies are ideal for effectively supporting an embodied and enactive pedagogical approach exploiting the best-suited sensory modality to teach a concept at school. This represents a great opportunity for making technologies, which are both grounded on a robust scientific evidence and tailored to the actual needs of teachers and students. Based on our experience in technology-enhanced learning projects, we propose six golden rules we deem important for catching this opportunity and fully exploiting it.